Comparison of the electronic and vibrational optical activity of a europium(III) complex - Wu, Tao; Hudecová, Jana; You, Xiao-Zeng; Urbanová, Marie; Bouř, Petr (Chemistry (Weinheim an der Bergstrasse, Germany), 2015)
The geometry and the electronic structure of chiral lanthanide(III) complexes are traditionally probed by electronic methods, such as circularly polarised luminescence (CPL) and electronic circular dichroism (ECD) spectroscopy. The vibrational phenomena are much weaker. In the present study, however, significant enhancements of vibrational circular dichroism (VCD) and Raman optical activity (ROA) spectral intensities were observed during the formation of a chiral bipyridine-Eu(III) complex. The ten-fold enhancement of the vibrational absorption and VCD intensities was explained by a charge-transfer process and the dominant effect of the nitrate ion on the spectra. A much larger enhancement of the ROA and Raman intensities and a hundred-fold increase of the circular intensity difference (CID) ratio were explained by the resonance of the λ = 532 nm laser light with the (7)F0 → (5)D0 transitions. This phenomenon is combined with a chirality transfer, and mixing of the Raman and luminescence effects involving low-energy (7)F states of europium. The results thus indicate that the vibrational optical activity (VOA) may be a very sensitive tool for chirality detection and probing of the electronic structure of Eu(III) and other coordination compounds.
Keywords: vibrational spectroscopy; lanthanides; electronic states; Raman spectroscopy; chirality; luminescence